Retour de flamme 04 : la fabuleuse enfance du cinéma - Bromberg, Serge; Georgiadès, Sylvie; Lange, Eric; Simon, Anne; Xavier, Ganachaud (Paris : Lobster Films, 2006)
- I'll say she is ; cop. 1931 (4 min) ##- La peine du talion / Gaston Velle ; cop. 1906 (4 min) ##- Alice in wonderland / W.W. Young ; cop. 1915 (27 min) ##- Trois soundies : Playmates, Male order, The sheik of araby ; cop. 1941-1944 (8 min) ##- La crue de la Seine ; cop. 1910 (4 min) ##- To spring / Hugh Harman ; cop. 1936 (8 min) ##- Les femmes députés ; cop. 1912 (7 min) ##- MGM promo reel / Hugh Harman, Rudolf Ising ; cop. 1936 (8 min) ##- Les gosses de la butte ; ca. 1916 (3 min) ##- La joie de vivre / Anthony Gross ; cop. 1934 (8 min) ##- Lizzies of the field / Del Lord ; cop. 1924 (9 min) ##- Philips Broadcast / George Pal ; cop. 1938 (4 min) ##- Le raid en avion autour du monde : épisode 4 / Willy Wolff ; cop. 1924 (21 min)
French or English language tracks with optional English or French subtitles.
film
Keywords: ACAD